A review of feudalism in Japan (Journal of Oriental Studies, 2021)
When one speaks of feudalism in Japan, one must always bear in mind that “Japanese” feudalism is as peculiar as “European” feudalism which exhibits different patterns in different countries at different times. The Japanese example is no exception in exhibiting different patterns and features at different regions and times. This study aims at discovering the periodic differences seen within the general framework of Japanese feudalism, especially in the domains under shogunal control by comparing the pre-Edo and Edo patterns of feudal structures. These differences in the administrative organization of the military and bureaucratic structures give Japanese feudalism a peculiar form different from Europe. Despite the seeming similarities attested by early modern European travelers to Japan and 19th century historians, as the comparative approach demonstrates, what was called as Japanese feudalism by the early western visitors of Japan was in fact a culmination of a centuries long process. This article approaches the theoretical framework of Japanese feudalism in a comparative perspective between different periods rather than trting it as a static, unchanging phenomenon, or trying to explain it in a Eurocentric framework by drawing a paradigm that confoms mainly to European norms of feudalism.